Knowledge and Infection Control practices Regarding Healthcare-Associated Infection among Healthcare Workers - Ikramullah, Anwar Shah, Danish Mehmood, Sardar Alam, Akber Alam, Barkat Ullah, Waqar Ali , (Pakistan Journal of Medical & Health Sciences, 2023)
Aims: To determine the knowledge and practices regarding healthcare-associated infection among healthcare workers and to make recommendations based on results to prevent healthcare-associated infection. Methodology: A descriptive correctional study was conducted in Burn and Trauma Center Peshawar, Pakistan. Data were collected from 162 healthcare workers through a questionnaire. Data was collected through a universal sampling technique. This study was permitted by the Ethical Review Board of Hayatabad Medical Complex Peshawar, Pakistan. This study was also granted by the Institute of Management Sciences (IM Sciences) Institutional Ethical Review Board (IRB) in Peshawar Pakistan. Knowledge and inflectional control practices regarding healthcare-associated infection were determined through frequency and percentage methods. To calculate the association between knowledge and profession, gender and knowledge, and profession and knowledge Chi-Square test was applied. Data were analyzed through SPSS 26 version. Result: The age of the participants was divided into three groups from 20-30 years 117 participants, 31-40 39 participants, and 41-50 are 6 participants. The majority of the participants are Female 101(62.3%) and 61 males (37.7%). The majority are Nurses 83(51.2%) Doctors 39(24.1%) Paramedics 40(24.7%). The knowledge of doctors was good regarding healthcare-associated infection as compared to Nurses and Paramedics, but the practices of overall healthcare workers were good. The results of the study show that Doctors have good knowledge compared to Nurses, and Nurses have good knowledge compared to Paramedics regarding HealthCare-associated infection. Conclusion: The finding of the study showed that doctors have good knowledge than Nurses and Paramedics. The practices of overall healthcare workers were good. Keywords: Healthcare-associated infection, Healthcare worker, Knowledge, Practices